Translation and cross-cultural adaptation of the Brazilian version of the Hospital Survey on Patient Safety Culture: initial stage - Reis, Claudia Tartaglia; Laguardia, Josué; Martins, Mônica (Cadernos de saúde pública, 2012)
Patient safety culture assessment allows hospitals to identify and prospectively manage safety issues in work routines. This article aimed to describe the cross-cultural adaptation of the Hospital Survey on Patient Safety Culture (HSOPSC) into Brazilian Portuguese. A universalist approach was adopted to assess conceptual, item, and semantic equivalence. The methodology involved the following stages: (1) translation of the questionnaire into Portuguese; (2) back-translation into English; (3) an expert panel to prepare a draft version; and (4) assessment of verbal understanding of the draft by a sample of the target population. The questionnaire was translated into Portuguese, and the scale's final version included 42 items. The target population sample assessed all the items as easy to understand. The questionnaire has been translated into Portuguese and adapted to the Brazilian hospital context, but it is necessary to assess its measurement equivalence, external validity, and reproducibility.